No evidence for the association of DRD4 with ADHD in a Taiwanese population within-family study - Huang Yu-Shu; Chen Chih-Ken; Xu Xiaohui; Brookes Keeley-Joanne; Wu Yu-Yu; Asherson Philip (BMC, 2005)
Abstract Background Attention Deficit Hyperactivity Disorder (ADHD) is a prevalent and highly heritable childhood disorder. The dopamine D4 receptor (DRD4) gene has shown a genetic association with ADHD in Caucasian populations with meta-analysis indicating a small but significant effect across datasets. It remains uncertain whether this association can be generalised to non-Caucasian ethnic groups. Here we investigate two markers within the DRD4 gene in a Taiwanese population, the exon 3 variable number tandem repeat (VNTR) and a 5' 120 base-pair duplication. Methods Within-family transmission disequilibrium tests of association of the 5' 120 base-pair duplication, and exon 3 VNTR in a Taiwanese population. Results No evidence of association of ADHD with either polymorphism in this population was observed. Conclusion The DRD4 gene markers investigated were not found to be associated with ADHD in this Taiwanese sample. Further work in Taiwanese and other Asian populations will therefore be required to establish whether the reports of association of DRD4 genetic variants in Caucasian samples can be generalised to Asian populations.